(untitled) (Journal of Medicine, 2008)
Aim of this study was to determine bacteriological pattern and there antibiotic sensitivity in UTI. The retrospective study carried out in department of internal medicine of BIRDEM on 300 consecutive patients with or without Diabetes Mellitus and whose urine culture shows growth of >105 organism/ml of urine, during the period from January 2006 to July 2007. A total of 300 patients were included in the study. The highest number of isolates was E.coli (62%,184) followed by Klebsiella (17%,50),Pseudomonas(6%,19), Enterococcus(8%, 23), Staphylococcus (3%, 10), Proteus (1%, 4) respectively in patient with DM(N-261) or without DM(N-39).All of these isolates were highly sensitive to Imipenem(96%) while some were high to moderate sensitive to other antibiotics. E.coli isolates showed high sensitivity to Aminoglycosides (72%, 133), Nitrofurantoin (70%, 129), and third generation Cephalosporin (61%, 112). Klebsiella was observed highly sensitive to third generation Cephalosporin (29%, 58) AND Nitrofurantoin (30%, 60). Â DOI = 10.3329/jom.v8i1.1373 J MEDICINE 2007; 8 : 10-13